Isolasi Dan Karakterisasi Bakteri Asam Laktat Dari Usus Udang Penghasil Bakteriosin Sebagai Agen Antibakteria Pada Produk-Produk Hasil Perikanan - Romadhon, Romadhon; Subagiyo, Subagiyo; Margino, Sebastian (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
Lactid Acid bacteria are capable of fermenting sugars or carbohydrates to produce lactic acid in large numbers. The characteristics of lactic acid bacteria in general are cells reacted positively to the Gram  stain, catalase react negatively and do not form spores. And fermentation of glucose would result Iaktat acid. Isolation of lactic acid bacteria carried in the intestines of three species of shrimp that Tiger Shrimp (Penaeus monodon), shrimp Seker (Metapenaopsis sp.), Guts White shrimp (Penaeus merguensis). Selection of bacteriocin -producing lactic acid bacteria were in a qualitative and semi-quantitative (pitting) in MRS medium. Selected isolates were identified by morphological characteristics, biochemical, physiological, A number of 209 isolates were isolated from three species of shrimp. The results of the qualitative selection there were 54 isolates produced bacteriocins. The results of the quantitative selection of 54 isolates produced 24 fine isolates.  From the 24 isolates there are 2 isolates seed SFE-7 (33) and P12A (25). Characteristics of seed isolates had morphological characteristics of spherical shape, cell arrangement tetrad, gram positive, negative motility. While the results of the biochemical approach to gram-negative, catalase negative,  homofermentative (no gas in the fermentation of glucose), can ferment D-Galactose, D-Glucose, D-mannose, D-lactose. Physiological approaches to isolate growth SFE-7 (33) and P12A (25) can be generated that both isolates able to live in the range of 4 ° C to 50 ° C, in the range of pH between 4-10, and able to grow at levels of 5-10% NaCl . Based on these characteristics can be inferred featured isolates was Pediococcus acidilactici Key words: Lactid Acid Bacteria, intestine of shrimp, Pediococcus acidilactici